A new species of Sphaeronemoura (Plecoptera: Nemouridae) from China and additions to three other species of the genus - Zhao, Meng-Yuan; Du, Yu-Zhou (Zootaxa, 2020)
A new species of the nemourid genus Sphaeronemoura, S. tetragona Du & Zhao, sp. nov. is described from Hunan Province of southeastern China. The new species is illustrated and compared to the other similar species of this genus. Additional illustrations and records for S. songshana Li & Yang, 2009, S. multicurvata Li, Li & Yang, 2020, and S. grandicauda (Wu, 1973) are also provided.